2002
DOI: 10.1038/sj.hdy.6800117
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical analysis of genetic structure in Spanish donkey breeds using microsatellite markers

Abstract: The hierarchical population structure of five, native-Spanish donkey breeds (Andaluza, Catalana, Mallorquina, Encartaciones and Zamorano-Leonesa) has been studied using Fstatistics. In addition, nine Moroccan asses and 24 Merens breed horses were included in the analysis. Data came from 15 DNA microsatellites. The analysis shows that Spanish donkeys are substructured at both hierarchical levels studied, among breeds and within breeds (between subpopulations). In the whole population, the deficit of heterozygot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 20 publications
2
18
0
1
Order By: Relevance
“…In contrast, the locus HMS1 was found to be monomorphic in both Chinese and Spanish donkeys (Aranguren-Méndez et al, 2002). Generally, the Chinese donkey shows relatively higher genetic diversity than the Spanish donkey at the seven polymorphic loci investigated in the current study.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…In contrast, the locus HMS1 was found to be monomorphic in both Chinese and Spanish donkeys (Aranguren-Méndez et al, 2002). Generally, the Chinese donkey shows relatively higher genetic diversity than the Spanish donkey at the seven polymorphic loci investigated in the current study.…”
Section: Discussionmentioning
confidence: 44%
“…Among the 10 microsatellites investigated in this study, the PIC of HTG4 and HMS5 were found to be 0.40 and 0.53 in five endangered Spanish donkey breeds, respectively, while both were monomorphic in Chinese donkey breeds (Aranguren-Méndez et al, 2002). In contrast, the locus HMS1 was found to be monomorphic in both Chinese and Spanish donkeys (Aranguren-Méndez et al, 2002).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…To date, the genetic diversity of indigenous donkey breeds in Spain (Aranguren-Mendez et al 2001;Aranguren-Mendez et al 2002), Croatia (Ivankovic et al 2002), Italy (Bordonaro et al 2012;Colli et al 2013;Matassino et al 2014), America (Jordana et al 2015), northeast Africa, the Near East and the Arabian Peninsula (Rosenbom et al 2015) has been evaluated using microsatellite markers, and these results of evaluation are crucial for making further conservation strategy. On the other hand, the origin of the species and evolutionary relationship between donkey breeds were analyzed using the mitochondrial DNA markers (Ivankovic et al 2002;Lopez Lopez et al 2005;Chen et al 2006;Zhang et al 2010;Han et al 2014;Perez-Pardal et al 2014), and these results hinted that the modern donkey (including Chinese donkey) has an African maternal origin.…”
mentioning
confidence: 99%